2021
DOI: 10.1017/s0305000920000641
|View full text |Cite
|
Sign up to set email alerts
|

Structural and interactional aspects of adverbial sentences in English mother-child interactions: an analysis of two dense corpora

Abstract: We analysed both structural and functional aspects of sentences containing the four adverbials “after”, “before”, “because”, and “if” in two dense corpora of parent-child interactions from two British English-acquiring children (2;00–4;07). In comparing mothers’ and children's usage we separate out the effects of frequency, cognitive complexity and pragmatics in explaining the course of acquisition of adverbial sentences. We also compare these usage patterns to stimuli used in a range of experimental studies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(145 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, however, the preference for beginning with the main clause was far stronger for sentences containing before, where that order preserved iconicity than for sentences containing after, where an initial main clause creates a non-iconic interpretation. One additional phenomenon worth noting (which was not discussed in detail in DeRuiter et al, 2021) is that the present moment was often used as one of the times being sequenced, particularly for the connective before: before now; did you ever do that before? These utterances suggest that in typical usage, one common anchor point for creating temporal sequences in a model is the here-and-now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, however, the preference for beginning with the main clause was far stronger for sentences containing before, where that order preserved iconicity than for sentences containing after, where an initial main clause creates a non-iconic interpretation. One additional phenomenon worth noting (which was not discussed in detail in DeRuiter et al, 2021) is that the present moment was often used as one of the times being sequenced, particularly for the connective before: before now; did you ever do that before? These utterances suggest that in typical usage, one common anchor point for creating temporal sequences in a model is the here-and-now.…”
Section: Discussionmentioning
confidence: 99%
“…A final element that influences children's comprehension of temporal connectives is the specific words themselves: temporal orders that are conveyed using the connective after tend to be more difficult for children to understand than those that are conveyed with before (E. V. Clark, 1971;DeRuiter et al, 2018;Pyykkönen & Järvikivi, 2012;Pyykkönen et al, 2003). DeRuiter et al (2021) attributed this effect to differing patterns of use in children's input. They examined dense corpora of two parent-child dyads and found that while before and after appeared at similar rates overall, before was used more consistently to order two full clauses (before the girl went outside, she ate a donut).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, future research could include the factor givenness to see if the event-semantic kindergarten-path effect can be modulated by presenting the sentences in given-before-new contexts. Finally, future research should examine the role of frequency of the connectives in both clause orders in children's input across languages (for before and after in English, see de Ruiter et al, 2021). Studies of connective use based on child corpora of Greek (Baslis, 1994;Stephany, 1997) have analyzed children's productions but not the adult speech directed to children, so we could not incorporate this aspect in our analysis.…”
Section: Limitationsmentioning
confidence: 99%
“…Since the 70s, researchers have proposed different explanations to account for the results (see de Ruiter et al, 2018ade Ruiter et al, , 2021, but to date, there is no consensus on which linguistic properties of the sentences cause the most difficulty for the language learner. This may be because studies often tested children of different ages and with different methods, making a close comparison across ages and experimental tasks difficult.…”
Section: Introductionmentioning
confidence: 99%